Solomon Islands : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This report describes economic developments in the Solomon Islands during the 1990s. Developments in the real sector were dominated by a broad-based export boom, which stemmed, in large part, from a continuing increase in the rate of extraction of forestry resources. Although economic growth was spurred by surging fish exports in 1994-95, logging also made a significant contribution to growth, with log exports rising to a new record in 1995. Inflation eased somewhat in 1995, reflecting slowing import price increases and an increasing supply of local food crops.